Strategic Management Processes and Performance of Public Technical and Vocational Education and Training Institutions at Kiambu County, Kenya - Waititu, Sammy; Lanoi, Rahab; Mwangi, Elias (European Journal of Business and Strategic Management, 2025)
Purpose: The overall objective of the study was to understand the role strategic management processes play in Technical and Vocational Education and Training Institutes performance in Kiambu County of Kenya. Methodology: The study made use of descriptive survey to conduct the research. The targeted population of the research was a population of 8 TVETs in Kiambu County and as well 675 trainers. Census sample was applied in which all the TVET institutions in Kiambu County were sampled in the study. Based on the formula develop by Yamane, 251 trainers were picked as a sample size. Standardized questionnaires were used by the researchers to get the primary data points of the trainers. The description of descriptive statistics was in form of percentages alongside means and standard deviation that were presented using figures but utilizing tables and pie chart in representation. The inferential analysis employed in the research involved correlation and multiple linear regression model to prove the correlations among study variables. Findings: Based on the analysis, it was determined that goal setting (r=0.247, β= 0.063, p<0.05), strategic analysis (r=0.312, β= 0.081, p<0.05), strategy formulation (r=0.197, 0.001, p<0.05), strategy implementation (r=0.292, 0.124, p<0.05) and strategy evaluation and control (r=0.42). The conclusion made was that all the indicators of strategic management process considered in the study have significant impact on the performance TVET institutions in Kiambu County. Unique Contribution: Based on the results, the research suggested that the TVET institutions within Kiambu County ought to increase the levels of stakeholder engagement and communication during goal setting processes, institutionalize frequent strategic analysis and evidence-based planning, and make strategies actionable and familiar.